Magnesium-ion batteries for electric vehicles: Current trends and future perspectives - Shah, Raj; Mittal, Vikram; Matsil, Eliana; Rosenkranz, Andreas (Advances in mechanical engineering, 2021)
Lithium-ion batteries have enabled electric vehicles to achieve a foothold in the automobile market. Due to an increasing environmental consciousness, electric vehicles are expected to take a larger portion of the market, with the ultimate goal of supplanting traditional vehicles. However, the involved costs, sustainability, and technical limitations of lithium-ion batteries do create substantial obstacles to this goal. Therefore, this article aims at presenting magnesium-ion batteries as a potential replacement for lithium-ion batteries. Though still under development, magnesium-ion batteries show promise in achieving similar volumetric and specific capacities to lithium-ion batteries. Additionally, magnesium is substantially more abundant than lithium, allowing for the batteries to be cheaper and more sustainable. Numerous technical challenges related to cathode and electrolyte selection are yet to be solved for magnesium-ion batteries. This paper discusses the current state-of-the-art of magnesium-ion batteries with a particular emphasis on the material selection. Although, current research indicates that sulfur-based cathodes coupled with a (HMDS)2Mg-based electrolyte shows substantial promise, other options could allow for a better performing battery. This paper addresses the challenges (materials and costs) and benefits associated with developing these batteries. When overcoming these challenges, magnesium-ion batteries are posed to be a groundbreaking technology potentially revolutionizing the vehicle industry.